2022
DOI: 10.20885/ejem.vol14.iss1.art9
|View full text |Cite
|
Sign up to set email alerts
|

Islamic banks credit risk performance for home financing: Before and during Covid-19 pandemic

Abstract: Purpose ― This study aims to assess the home financing credit risk performed by Islamic banks in Indonesia. Methods ― A panel dynamic analysis is adopted to measure the bad loan performance before and during the Covid-19 pandemic. The observation period started from January 2016 to September 2020 with 1,881 observation periods of monthly panel data from the province level. Findings ― The study finds a difference in bad loan performance before and during the Covid-19 pandemic. Before this pandemic, inflation ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…According to the finding, during all periods, inflation does not have a significant influence on NPF in all models. The finding is different from Fakhrunnas et al (2021), andAnto et al (2022) stated that inflation is the determinant of NPF's value in the Indonesian Islamic bank. Moreover, FDR has a positive and significant impact on NPF in investment financing.…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…According to the finding, during all periods, inflation does not have a significant influence on NPF in all models. The finding is different from Fakhrunnas et al (2021), andAnto et al (2022) stated that inflation is the determinant of NPF's value in the Indonesian Islamic bank. Moreover, FDR has a positive and significant impact on NPF in investment financing.…”
Section: Resultscontrasting
confidence: 68%
“…Hence, the bank is considered to have better risk management compared to a smaller bank, particularly in Java Island. Other related financial performances, such as financing to deposit ratio and asset size of the banks, possess a pivotal role in determining the Islamic bank performance, particularly in NPF value (Sutrisno et al, 2020;Anto et al, 2022). The impact of Islamic banks' assets on banking performance is also highlighted by Ibrahim and Rizvi (2017), who employed cross countries analysis and the impact of financial performance on Islamic bank financing for SMEs studied by Aysan et al (2016) in the case of Turkey.…”
Section: Fakhrunnas and El Hasanahmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, there were 1947 observation periods. The study adapted the conceptual framework of Boyd et al, (2001) and Anto et al, (2022) to model the relationship among the observed variables:…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Anto et al, (2022) argued that regional effect is important to determine the Islamic banking performance. The vulnerability to macroeconomic variable such as regional inflation and the performance of Islamic bank vary across provinces in Indonesia.…”
Section: Previous Research and Hypotheses Developmentmentioning
confidence: 99%